2000
DOI: 10.1007/s002149900093
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on "Density functional approach to the frontier-electron theory of chemical reactivity"

Abstract: The Fukui function, f r, was proposed as a tool for deducing the relative reactivity of dierent positions in a molecule by Parr and Yang in 1984.Herein we sketch the theory of the Fukui function, with special emphasis on its logical motivation, interpretation, qualitative characteristics, and practical computation. We conclude with some words about the Fukui function's extensions, limitations, and importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(81 citation statements)
references
References 36 publications
0
81
0
Order By: Relevance
“…Based on more intuitive considerations on the E = E(N) curve in the early days, its intrinsic value was stressed by the fundamental work by the famous Perdew, Parr, Levy, Balduz paper, 23,24 pointing out the continuous nature of the E = E(N) curve as a piecewise linear function in the canonical example. 25 Computational techniques yielding this property should, however, obey strict conditions and be of the many electron self-interaction free type 26 (for a recent in depth analysis see Refs. [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Based on more intuitive considerations on the E = E(N) curve in the early days, its intrinsic value was stressed by the fundamental work by the famous Perdew, Parr, Levy, Balduz paper, 23,24 pointing out the continuous nature of the E = E(N) curve as a piecewise linear function in the canonical example. 25 Computational techniques yielding this property should, however, obey strict conditions and be of the many electron self-interaction free type 26 (for a recent in depth analysis see Refs. [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, the frontier electron theory has its own limitations. Sometimes, reactivity may be determined by strong electrostatic forces rather than by frontier orbitals, especially for reactions associated with an aromatic system . In regard to the above analysis, it can be concluded that the carbon atoms in the benzene ring are all reactive to be attacked by radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The Fukui function was defined as follows: Where was electronic density, N was number of electrons and ν was external potential exerted by the nuclei. The concept was first described by Fukui in 1952 [93] and a corresponding definition with the Density functional theory (DFT) was given in 1984 [89, 91]. However, the condensed Fukui function was restricted to an atom within a molecule rather than a point in 3D space [9498].…”
Section: Methodsmentioning
confidence: 99%